2021
DOI: 10.3390/agronomy11071420
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Small Grains Crops in Enhancing Biofortification Breeding Strategies for Human Health Benefit

Abstract: Nutrition is a source of energy, and building material for the human organism. The quality of food has an effect on the quality of individual life. Minerals and vitamins participate in various catalytic and regulatory functions of the main metabolic processes: absorption, transport, redox and biosynthesis of organic compounds, genetic information transfer, etc. Regular consumption of dietary fibers like β-glucans and oat-specific phenolics, antioxidants, and avenanthramides, stimulate innate and acquired immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
0
11
0
1
Order By: Relevance
“…The concept of biofortification of food crops or cereals has yet to attract sufficient attention in Russia, either in research or in the plant-breeding community. Recent reviews by Loskutov and Khlestkina [23] and Shelenga et al [24], and the study of Bityutskii [7] demonstrated that there is an understanding of the importance of the nutritional value of wheat, barley, and oats, taking into consideration concentrations of essential microelements. However, this has not yet been converted into integrated biofortification programs for wheat and other staple crops.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of biofortification of food crops or cereals has yet to attract sufficient attention in Russia, either in research or in the plant-breeding community. Recent reviews by Loskutov and Khlestkina [23] and Shelenga et al [24], and the study of Bityutskii [7] demonstrated that there is an understanding of the importance of the nutritional value of wheat, barley, and oats, taking into consideration concentrations of essential microelements. However, this has not yet been converted into integrated biofortification programs for wheat and other staple crops.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of the studied characteristics in oat cultivars can be significant, with a 2.7-to 10.5-fold difference between the maximum and minimum values, which implies a search for promising sources of a high content of important micronutrients in grain to serve as a basis for the development of new high-quality oat cultivars (Bityutskii et al, 2020). Wide differences between cultivars of the same crop can be effectively used in breeding programs to increase the content of micronutrients in grain Shelenga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Eating and cooking quality of rice grain is generally determined by three physicochemical indices containing amylase content (AC), gel consistency (GC), and gelatinization temperature (GT) [14,16]. Rice grain nutritional quality mainly comprises the grain protein content (GPC), and contents of fats, amino acids, vitamins, and other micronutrients [17][18][19]. These research efforts will be able to contribute to improving the quality of rice grains in future breeding programs by acquiring the basic genetic knowledge of grain components.…”
mentioning
confidence: 99%